Prospective evaluation of remifentanil-propofol mixture for total intravenous anesthesia: A randomized controlled study - Bakan, Mefkur; Umutoglu, Tarik; Topuz, Ufuk; Guler, Emine Yilmaz; UYSAL, HARUN; UYSAL, HARUN; Ozturk, Erdogan (My University, 2021)
Application of total intravenous anesthesia (TIVA) may be considered as unpractical when compared with inhalational anesthesia. Although it is mostly not recommended, mixing intravenous agents is popular in clinical practice. The aim of the present study was to investigate the suitability of using remifentanil-propofol mixture (MIXTIVA) for TIVA. Adult patients with an American Society of Anesthesiologists grade of I-II scheduled for elective thyroidectomy were randomly allocated to 3 groups (n=32 for each) to receive TIVA with remifentanil and propofol infusions separately (control group, Group I) or with MIXTIVA infusion that contained remifentanil/propofol at a proportion of 2/1,000 or 3/1,000 (remifentanil concentration, 20 or 30 mu g/ml in 1% propofol in Group II or Group III, respectively). The extubation time (the primary outcome of the study), the orientation time and number of patients in whom intraoperative hypotension, hypertension or bradycardia episodes were encountered during anesthesia were comparable among the groups. The mean remifentanil infusion rate in Group III was significantly higher than that in the other groups. The mean propofol infusion rates and mean bispectral index (BIS) scores during anesthesia were comparable among groups. Hypotension accompanied with a high BIS was encountered in one patient in Group III. In conclusion, compared to the standard TIVA technique using separate drug infusions, MIXTIVA infusion used for thyroidectomies did not result in any statistically significant difference in recovery and clinical outcomes. This technique may be considered as a practical implementation for busy ambulatory centers performing general anesthesia.
Keywords: bispectral index monitoring; intravenous admixture; propofol; propofol-remifentanil mixture; remifentanil; total intravenous anesthesia